More than Casinos: California Indian Culture, Contributions and Communities - Multiple
More Than Casinos: California Indian Culture, Contributions and Communities is a collection of contemporary photographs and traditional works of art that was on display at Kellogg Library September 25-December 14, 2012. The exhibit communicated multiple Native points of view on critical historical and contemporary issues within California Indian communities, engaging CSUSM students in discovering, viewing, listening to, and analyzing popular historic and contemporary notions about California Indian tribes. The purpose of More Than Casinos is to challenge misinformation and misconceptions in a dynamic expression of California Indian history, cultures and contemporary issues. This virtual exhibit includes the installation and mixed media artwork be artist Gerald Clarke; the large scale oil paintings of artist Robert Freeman; contemporary pieces on loan from the California Indian Culture and Sovereignty Center; and historical artifacts on loan from the California Indian Museum and Cultural Center. Some of the items in this collection are handmade gathering baskets, Gourd Rattles, an assortment of children books, a traditional willow skirt and collar (items of clothing usually worn on special occasions), a collection of beautiful oil and acrylic paintings, and a Shinny Stick and Ball, which were used by different villages to play against each other during large gatherings. The objective of the items on display was to shed light on the true Native American identity and culture.